1946
DOI: 10.1152/ajplegacy.1946.146.4.567
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Epinephrine and Physostigmine on the Response of Striated Muscle to Acetylcholine and Potassium

Abstract: The APS Journal Legacy Content is the corpus of 100 years of historical scientific research from the American Physiological Society research journals. This package goes back to the first issue of each of the APS journals including the American Journal of Physiology, first published in 1898. The full text scanned images of the printed pages are easily searchable. Downloads quickly in PDF format.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

1950
1950
1958
1958

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 0 publications
1
1
0
Order By: Relevance
“…When this is suppressed by ergotoxine, the potentiation is revealed. This is in agreement with the observations of Dale & Gaddum (1930), Burn (1945), Torda & Wolff (1946), Ellis & Beckett (1955) and Hutter & Loewenstein (1955), which were based mostly on experiments with muscles in vitro.…”
Section: Discussionsupporting
confidence: 93%
“…When this is suppressed by ergotoxine, the potentiation is revealed. This is in agreement with the observations of Dale & Gaddum (1930), Burn (1945), Torda & Wolff (1946), Ellis & Beckett (1955) and Hutter & Loewenstein (1955), which were based mostly on experiments with muscles in vitro.…”
Section: Discussionsupporting
confidence: 93%
“…Various hypotheses have been suggested to explain this complex phenomenon (Torda & Wolff, 1946): they include reduction of serum cholinesterase (Tsuji, 1932) and changes in the extracellular concentration of potassium. It has also been suggested that adrenaline, by favouring the production of lactic acid and the reconstitution of phosphagen (Nachmansohn, Waizer & Lipmann, 1936), causes changes in the effector apparatus which increase its sensitivity to acetylcholine.…”
Section: J Malm9jacmentioning
confidence: 99%